An Automatic Identification System of Human Skin Irritation - Abdul Fadlil (Universitas Ahmad Dahlan, 2010)
Quantitative characterization of human skin irritation is important but it is difficult task to be done. Recently, an identification of human skin is still doing manually. Indeed, the identification of the human skin irritation sample can be very subjective. The analysis of the skin irritation could be conducted using biochemical test, but it is not simple. In this research, a new approach of an automatic human skin identification system based on image pattern recognition is developed to obtain a decision of sample test (whether it has irritation or not). This system design was developed using the following features extraction: gray level histogram (GLH) feature and texture gray level co-occurrence matrices (GLCM). Meanwhile, for a classification process, using the following distance metric: Manhattan distance and Euclidean distance, or learning vector quantization neural network (LVQ-NN). The combination between feature extractor and classifier methods proposed was used to evaluate the performance system. The experimental results show that the best accuracy for 83.33% was obtained when design system was implementated using GLH or GLCM features through LVQ-NN classifier.